Historical and new insights into pathogenesis of type 1 diabetes (2). (23rd April 2021) - Wong, F S; Tree, T I
Summary: In this second and final part of the collection of articles for the Immunology of Diabetes Society review series on insights into pathogenesis of type 1 diabetes, we present two articles. The first of these covers a debate that took place in the Immunology of Diabetes Society meeting in London 2018, in which five investigators presented a case for specific immune cells/targets to be the 'Achilles Heel of type 1 diabetes'. The second article presents further insights into the generation of post-translationally modified peptides. It focuses upon mechanisms and processes that lead to new potentially autoantigenic targets for CD8 + T cells, and complements the review of new hybrid peptide targets for CD4 + T cells in the first part of our series.